P190 REAL-WORLD USE OF IMMUNOSUPPRESSIVES AMONG PATIENTS WITH INFLAMMATORY BOWEL DISEASE TREATED WITH VEDOLIZUMAB. (18th January 2018) - Raluy-Callado, Mireia; Carroll, Robert; Curtis, Rebecca; Khalid, Javaria Mona; Patel, Haridarshan
Abstract: Background: Immunosuppressives (IM) are often used as maintenance therapy to reduce the risk of relapse in patients with inflammatory bowel disease (IBD). Vedolizumab (VDZ), a humanized monoclonal antibody that selectively targets the α4β7 integrin, has been approved for the treatment of moderately-to-severely active Crohn's disease (CD) and ulcerative colitis (UC). This study aimed to assess the real-world use of IM therapy and compare outcomes in IBD patients with or without a history of IM use, who initiated VDZ treatment in the US. Methods: The Explorys Universe database was used to identify all IBD patients >18 years of age who initiated VDZ therapy between 05/20/2014 and 02/22/2016 (the date of VDZ initiation was the assigned index date) and had 365 days of available data pre- and post-index date (follow-up). Patients were stratified by use of IMs at any point in their treatment history before the index date. Key outcomes in the follow-up period included the use of IMs and the incidence of IBD-related surgeries, hospitalizations, and flares. Results: A total of 567 patients (68% with CD, 32% with UC) aged 44 ± 15 years (59% female) were included. Overall, 55% had prior use of IMs and 65% received tumor necrosis factor antagonist therapy before starting VDZ therapy. Patients initiated VDZ at 4.5 ± 3.6 years after initial diagnosis (Table 1). During maintenance, 61% and 87% of patients with and without a history of IM use, respectively, did not use IMs. Among VDZ patients with vs those without a history of IM use, there was a trend of increased flares (39% vs 30%, p=0.034), hospitalizations (22% vs 20%, p=0.605), and surgeries (11% vs 7%, p=0.103). Conclusion: Most patients with a history of IM use did not use IM therapy after initiating VDZ in a real-world clinical setting. The use of IMs after initiating VDZ was also low among patients without a history of IM use. Low rates of healthcare resource utilization were observed with or without prior IM use.